Monitoring brain damage using bioimpedance technique in a 3D numerical model of the head. Issue 5 (May 2015) - Cohen, Rotem; Abboud, Shimon; Arad, Marina
Highlights The feasibility of electrical impedance technique for monitoring brain damage was studied using a realistic 3D numerical model of the head. Left-right asymmetry in the surface potentials was calculated for head model with damaged regions in the brain. Correlation was found between the location of the damaged region and the electrodes with significant asymmetry. The electrical conductivity and the size of the damaged tissue has an effect on the left-right asymmetry of the surface potential.